TINJAUAN ATAS PENYUSUNAN LAPORAN PERTANGGUNGJAWABAN BENDAHARA PENERIMAAN MENGGUNAKAN SISTEM APLIKASI SATKER (SAS) PADA BADIKLAT PKN BPK RI - Kinanti Ananda Pujiastuti (2021)
Financial Administration is an activity in managing money in an orderly, efficient and effective manner to achieve goals in accordance with organizational goals. Financial administration is a process that involves managing the organization's money and carrying out the functions of budgeting, provision, accounting and accountability for work in the context of working together a group of people to achieve certain goals. The purpose of this Final Project Report is to find out how to prepare the Accountability Report for the treasurer of receipts using the Satker Application System (SAS) at Badiklat PKN BPK RI and to find out what documents are involved in making the accountability report at the Badiklat PKN BPK RI.The existence of the SAS application makes it very easy for users, where the implementation of state finances should be carried out openly and also follow the rules of financial management applied in Indonesia. SPRINT also makes it easy for users to re-upload LPJ.